Evaluation of the antioxidant effects of melatonin on the larynx mucosa of rats exposed to environmental tobacco smoke. (4th February 2016) - Donmez, Z.; Yigit, Ö.; Bilici, S.; Dursun, N.; Gul, M.; Dastan, S.D.; Uzun, H.
Abstract : Objectives: This study's aim was to investigate the effect of melatonin in terms of mitigating the effects of smoking on the laryngeal mucosa of rats exposed to environmental tobacco smoke. Design: Rats were divided into four groups: Melatonin + Smoking group exposed to smoke with melatonin; Smoking group exposed to smoke without melatonin; Saline group not exposed to smoke without melatonin; Melatonin group not exposed to smoke with melatonin. CuZn‐superoxide dismutase (CuZn‐SOD), catalase (CAT) and glutathione peroxidase (GSH‐Px) activities were evaluated in plasma and tissues. Tissues were also examined the changes of squamous hyperplasia, keratosis, parakeratosis and epithelial hyperplasia by light microscope and the ultrastructural changes by electron microscope. Results: Tissue SOD, CAT and GSH‐Px activities were significantly higher in Saline and Melatonin groups than Melatonin + Smoking and Smoking groups. Plasma CuZn‐SOD and CAT activities were significantly higher in Saline and Melatonin groups than Smoking group. Plasma GSH‐Px showed no significant difference. The rate of epithelial hyperplasia was significantly higher in Smoking group than the other groups. The rate of parakeratosis was significantly higher in Smoking group than the other groups. The epithelial cells in Melatonin + Smoking group displayed, normal cell structure similar to those in Saline group under electron microscope. Conclusions: The study shows that smoking induces substantial pathological changes in the laryngeal mucosa and melatonin may have some beneficial effects in partially reversing smoking‐induced laryngeal injury by inducing the expression of antioxidants; biochemical and histological outcomes also support these findings due to preventing tissue damage in laryngeal mucosa exposed to smoke.